THE DYNAMICS OF POLITICAL BEHAVIOR IN MADURA: From the Kingdom to the Digital Democracy Eras - Hidayaturrahman, Mohammad; Ubaid, Ahmad Hasan; Sinaga, Astriana Baiti; Sudarman, Sudarman (Ulul Albab: Jurnal Studi Islam, 2024)
The political history of Madurese society reflects dynamic changes across different periods. This study examines the political behavior of the Madurese people from the kingdom era in Sumenep, Bangkalan, and Pamekasan, through the Dutch colonial and post-independence periods, to the New Order and the digital democracy era of 2019. Using a descriptive qualitative approach, data were collected through document analysis and in-depth interviews with historians, cultural experts, and political experts. The findings reveal that Madurese political behavior has evolved significantly over time. During the kingdom era, it was marked by respect and obedience to kings. In the Dutch colonial period, political behavior shifted toward armed resistance against oppression. In the post-independence era, the focus was on resisting colonial influence, while in the New Order era, resistance targeted political manipulation. In the digital democracy era, political behavior became shaped more by psychological factors, emphasizing individual preferences and pragmatism. These transformations are driven by sociological factors, particularly religion, and later by psychological influences. The study highlights that voter behavior is dynamic, shaped by evolving social, economic, and technological contexts, providing insights into the fluid nature of political engagement.